Educational returns in the Colombian regions: an analysis using the Oaxaca-Blinder Decomposition - Quiñones Domínguez, Mauricio; Rodríguez Sinisterra, Juan Antonio (Sociedad y Economía, 2011)
Taking as reference the human capital theory examines regional differences, as indicator of changes in the income of individuals belonging to them. Were used for this purpose OLS estimates and the decomposition of Oaxaca-Blinder, correcting for selection bias by the method proposed by Heckman, using data from the Continuous Household Survey in the second quarter of 2006 for the thirteen cities Colombia. With reference Bogota region, evidence of changes in returns to education attributable to regional conditions, breaking what proportion is for the endowment of human capital and what the status of belonging to the respective region.